(untitled) (Revista Română de Jurnalism și Comunicare, 2025)
In a context where social networks are becoming an increasingly used platform for political communication, TikTok has become a central infrastructure for interaction between voters and political messages from representatives of such organizations, especially among the younger generations. This article explores the relationship between TikTok use and the electoral profiles of Romanian voters, based on a nationally representative survey in which 43% of respondents said they use the platform. The main purposes of using TikTok are watching humorous content (58%) and discovering general news (15%), while only 3% use it for political information. However, approximately 20% of active users say they take into account political information on TikTok “to a great extent” or “to a very great extent”. The article proposes a series of digital archetypes of voters – from the “passive user” to the “politicized consumer” – and analyzes how these digital behaviors overlap with voting intentions, especially in relation to parties occupying both the political mainstream and the opposition constituted as a sovereignist pole or with political figures such as Călin Georgescu – unknown to the general public until November 2024. Through a quantitative approach, the paper highlights the trends of “political infotainment” and the hybridization of civic space with that of digital entertainment. The study provides a framework for understanding new forms of electoral mobilization in a digital environment saturated with intense, short-term, algorithmic and emotional stimuli.